Breaking the chain of dependency: using Treaty Land Entitlement to create First Nations economic self-sufficiency in Saskatchewan - Major, Rebecca Ann (2010)
In the 1970’s, discussions began regarding the settlement of outstanding land claims from First Nations, the settling of Treaty Land Entitlement (TLE). The Office of the Treaty Commissioner (OTC) was developed to facilitate intergovernmental agreements with First Nations bands. This endeavour created discussions that led to the signing of the Treaty Land Entitlement Framework Agreement (TLEFA) in 1992. Lands purchased through TLE can be leased, creating revenues for the First Nations band. Those revenues can then be used to facilitate economic development and wealth creation for the band. It is through this access to capital that First Nations are starting to break their financial dependency on the Crown. It has been almost two decades since the signing of the TLEFA, and one can begin to measure the economic impact TLE has had for First Nations communities. Muskeg Lake Cree Nation (MLCN) is one such band that has been deemed successful, both by themselves and by outsiders, in the area of economic development. Success depends on a community developing an economic model that incorporates Aboriginal cultural values. By doing so, a cultural-oriented confidence is created, and this confidence can help foster economic success. The framework for this study is based around the Harvard Project on Indian Economic Development and its basis for economic success being founded on a community having confidence in their business model as it fits with their worldview. The methods employed in this study include a survey of primary and secondary documents in the area of TLE/TLEFA, and in economic development related to First Nations bands. Interviews were conducted with those involved in the signing and the overseeing of the TLEFA. Archival materials have been made available courtesy of Roy Romanow during his time as Attorney General for Saskatchewan. The research demonstrates that First Nations bands can break their financial dependency with the Crown through economic development strategies that are congruent with the First ...